Effect of microstructure and defects on fatigue behaviour of directed energy deposited Ti–6Al–4V. (November 2015) - Prabhu, A. W.; Vincent, T.; Chaudhary, A.; Zhang, W.; Babu, S. S.
<x content-type="archive" xml:space="preserve">Abstract</x> The fatigue behaviour of laser engineered net shaping (LENS) deposited Ti–6Al–4V is studied in the as built condition. The fatigue properties are measured, and the influence of microstructure and physical defects on fatigue performance is analysed through microscopy and fractography. Fine basketweave microstructure is obtained using a substrate with large equiaxed grains. The presence and location of unmelted particles are observed to significantly affect fatigue life. On the other hand, smaller gas porosity is not found to have major effect on the fatigue life. Further, the fatigue properties in a 'repair' condition are evaluated through samples consisting of LENS deposited parts joined to a preexisting wrought part. The properties are compared with the as built LENS parts.